2019
DOI: 10.1007/s00268-019-04925-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Composition on Surgical Outcome in Rectal Cancer Patients, a Retrospective Cohort Study

Abstract: Background Obesity is becoming a bigger health problem every year. Current research shows that the obesity-related metabolic problems are strongly associated with visceral fat and not subcutaneous fat. Visceral obesity (VO) is associated with a worse postoperative outcome in multiple fields of abdominal surgery. On the other hand, muscle mass is related to better postoperative outcome. In rectal cancer patients, we studied the influence of visceral obesity and muscle mass on postoperative complications. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 47 publications
(64 reference statements)
2
23
0
Order By: Relevance
“…The same counts for VAT or visceral obesity, which was found to be associated with postoperative complications , LOS , readmission , and 2‐year survival in some studies. However, in other studies, associations with overall postoperative complications , LOS , readmission , dose‐limiting toxicity , and long‐term survival were not found. The use of cutoff points and inclusion of all age groups could have contributed to the inconsistency of these results.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The same counts for VAT or visceral obesity, which was found to be associated with postoperative complications , LOS , readmission , and 2‐year survival in some studies. However, in other studies, associations with overall postoperative complications , LOS , readmission , dose‐limiting toxicity , and long‐term survival were not found. The use of cutoff points and inclusion of all age groups could have contributed to the inconsistency of these results.…”
Section: Discussionmentioning
confidence: 67%
“…Low muscle density has been associated with postoperative complications and long‐term survival , although other studies have found no associations with overall or severe postoperative complications and long‐term survival . The same counts for VAT or visceral obesity, which was found to be associated with postoperative complications , LOS , readmission , and 2‐year survival in some studies. However, in other studies, associations with overall postoperative complications , LOS , readmission , dose‐limiting toxicity , and long‐term survival were not found.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, within urology most prehabilitation studies have focussed upon reducing specific urological complications (e.g. urinary incontinence) [16] and not on general physiological parameters known to be associated with improved post-operative outcomes and return to preoperative status such as CRF [14], skeletal muscle mass [17] and body composition [18]. One consideration for all cancer prehabilitation regimes largely regardless of endpoint is that in the UK, the National Cancer Action Team specifies that first treatment (including surgery) should start within 31 days of the decision to treat [19].…”
Section: Introductionmentioning
confidence: 99%
“…PMI is a simple but reliable method of prognostic evaluation similar to SOFA. Body composition has recently been reported as a risk factor or prognostic factor for postoperative complications [3,5,24,25] early introduction of aggressive blood purification and medication may be necessary in the muscle loss group. In this study, the number of cases was limited because of the single-center design, and the ability to conduct sufficient studies appears limited.…”
Section: Discussionmentioning
confidence: 99%